Problems of Law Enforcement and Ideas of Paradigm Prophetic in Indonesia - Despan Heryansyah; Muhammad Hidayatullah (Faculty of Law, Jambi University, 2018)
Law enforcement portraits in Indonesia have not provided encouraging results. The reforms of 1998 in all aspects of the state including law have not always proceeded as planned. The fact that law continues to be legalistic-positivist is a major problem of law enforcement in Indonesia that never succeeded. Therefore, the reconstruction of such thinking model must first be done. As the law is not an independent entity separate from its association with other entities, however, the law is part of the life of society that can not be released away from social entities, politics and so on. The idea of ​​prophetic law is the right solution for the improvement of the Indonesian legal system. The prophetic paradigm is a set of theories that not only describe and transform social phenomena, nor simply change a thing for change, but more than that, it is expected to lead to change on the basis of ethical and prophetic ideals. Where in the basis of the conception of humanization, liberation, and transdensi as stated in the letter of Ali Imron: 110. The prophetic paradigm differs greatly from the positivist paradigm. The transcendence base, humanization orientation and liberation embedded in law enforcement will encourage its existence to always be total in making legal findings (ijtihad al hukmi) objective to be applied to a case. By making the paradigm of prefetics law as the base of law enforcement value in Indonesia, it is expected that law can really give a sense of justice to society which so far only limited to wishful thinking